Innovation, Entrepreneurship, and Economic Growth: A Proposed Framework - Minwir Al-Shammari; Waleed A. Aziz (International Journal of Scientific Research and Innovative Studies, 2024)
Business and governmental development strategies have made innovation and entrepreneurship part of their fundamental tenets in recent decades, especially after the 2007-2008 global financial crisis. It has grown in significance as the capacity to invent new products or services has become a more common descriptor of a successful business. However, the literature showed a gap in developing a framework that integrates innovation management (IM), entrepreneurship development (ED), and economic growth (EG). Academics have offered scattered perspectives on innovation and entrepreneurship from an ecosystem perspective. This paper adopts an exploratory analysis of 50 articles and books indexed in Scopus, the Web of Science, Google Scholar, and other renowned databases from 1990-2022 to propose a comprehensive framework that connects creative business ideas with entrepreneurial development and accelerated EG. Firms that succeed in turning novel concepts into commercially viable goods, services, processes, or technology are regarded as innovative entrepreneurs. Keywords: Entrepreneurship Development, Economic Development, Innovation Management, Proposed Framework.